Hospitalisations and emergency department visits in cancer patients receiving systemic therapy: Systematic review and meta‐analysis. (20th September 2018) - Prince, Rebecca M.; Powis, Melanie; Zer, Alona; Atenafu, Eshetu G.; Krzyzanowska, Monika K.
Abstract: Emergency department visits and hospitalisations (ED+H) during systemic therapy are undesirable for both patients and the health system. We undertook a systematic literature review and meta‐analysis to evaluate the frequency of unplanned all‐cause and treatment‐related ED+H among adults receiving adjuvant or palliative‐intent systemic therapy for all cancers. Randomised controlled trials (RCT) and observational studies (OS) reporting ED+H were identified from Medline and EMBASE from inception to June 2016. Quality was assessed using modified STROBE, CONSORT or PRISMA guidelines, depending on study type. A total of 112 OS (308, 662 patients) and 26 RCTs (16, 081 patients) met inclusion criteria. Most articles focused on palliative treatment (59%) delivered as first‐line, in breast, lung and colorectal cancers. Only 20 articles reported ED frequency. Treatment‐related and all‐cause hospitalisations were more common in routine practice than in RCTs (29% vs. 16% and 42% vs. 28% respectively); frequency varied by treatment intent and tumour site. Methodological issues were common, particularly poor definition of the at‐risk period. Hospitalisations are common, especially in unselected populations, but few articles report this and do so poorly. Routine, standardised reporting of ED+H during chemotherapy should be included in RCT reports and evaluated in routine care following adoption of new treatments.